Prohibiting Babel-A call for professional remote interpreting services in pre-operation anaesthesia information. - Gernot Gerger; Nikolaus Graf; Elisabeth Klager; Klara Doppler; Armin Langauer; Verena Albrecht; Aylin Bilir; Harald Willschke; David M Baron; Maria Kletecka-Pulker (PLoS ONE)
Introduction Language barriers within clinical settings pose a threat to patient safety. As a potential impediment to understanding, they hinder the process of obtaining informed consent and uptake of critical medical information. This study investigates the impact of the current use of interpreters, with a particular focus on of engaging laypersons as interpreters, rather than professional interpreters potentially affecting patient safety. A further objective is to explore the reliability of phone-based telemedicine in terms of the retention of important medical facts. Methods In three groups (N per group = 30), we compared how using lay or professional interpreters affected non-German speaking patients' subjectively perceived understanding (understood vs. not understood) and recollection (recollected vs. not recollected) of information about general anaesthesia. Proficient German speaking patients served as the control group. Statistical analyses (χ2 tests and binomial) were calculated to show differences between and within the groups. Results All three groups indicated similar, high self-reported levels of having understood the medical information provided. This was in stark contrast to the assessed objective recollection data. In the lay interpreter group, recollection of anaesthesia facts was low; only around half of participants recalled specific facts. For patients supported by professional interpreters, their recollection of facts about anaesthesia was significantly enhanced and elevated to the same level of the control group (fluent in German). Moreover, for these patients, providing information by means of phone-based telemedicine before anaesthesia yielded high levels of understanding and recollection of anaesthesia facts. Conclusion Phone-based telemedicine is a safe and reliable method of communication in the professional interpreter group and German speaking control group, but not in the lay interpreter group. Compared to lay interpreters, professional interpreters significantly improve patients' uptake of critical information about general anaesthesia, thus highlighting the importance of professional interpreters for patient safety and informed consent.